Avaliação do efeito da utilização de lavagem uterina com solução fisiológica ozonizada em éguas - Takakura, Giovanna Santesso (2020)
In view of the prevalence and importance of endometritis in equine breeding systems, the alternatives for treating this pathology are widely studied. This study was conducted to evaluate the anti-inflammatory effect of uterine lavage with ozonized saline solution on the endometrium. Thirty-three mares with low reproductive score were submitted to cytology and endometrial histology exams, previously and three days after treatments that consisted of uterine lavage with saline solution (n = 10) as a control treatment (TC) or with ozonized saline solution ( n = 23) (TO). The degree of inflammation was determined by the change in the count of polymorphonuclear neutrophils (PMNs). Comparing the data obtained in the endometrial cytology exams before and after treatment, there was no difference between treatments (p = 0.3301), in the TC treatment 50% of the animals showed improvement in the condition and in the TO 47.83%. However, according to the histological evaluation, it was found that the mares treated with ozonated saline obtained a decrease (p <0.0001) in the mean PMN count (1.16 ± 0.45) when compared to the mares that received CT (3.54 ± 1.29). In conclusion, this treatment modality can be used in animals with clinical and subclinical endometritis, and in the routine of embryo donors susceptible to persistent mating induced endometritis, decreasing the use of antimicrobials.